PENGARUH VARIASI TEKANAN REFRIGERANT TERHADAP KINERJA SISTEM AIR CONDITIONER SPLIT KONVENSIONAL - Mardiansah; Aripin Triyanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
An abstract The performance of an Air Conditioner can be influenced by the refrigerant charge. The problem arising from this is a decrease in the performance of the unit being used. The method used is to vary the refrigerant pressure value to obtain an appropriate value for the space in use. The aim of the research is to determine the recommended type of refrigerant and pressure for the split AC inside the room, achieve electrical energy consumption efficiency, and attain maximum room cooling. This research also assists in providing practical guidance for owners of conventional Split Air Conditioners and technicians in maintaining the optimal performance of their systems. The results of the research indicate that the highest temperature for the R22 type is at 26˚C and for R410A at 25˚C in a 3 x 3-meter room. The measured current value for R22 is 2.6 Ampere and for R410, it is 2.2 Ampere, with the voltage for R22 at 222 V and R410A at 221 V.